Pengaruh Penerapan Sistem Informasi Pemerintahan Daerah (SIPD) dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan: Studi pada Organisasi Perangkat Daerah (OPD) Provinsi Gorontalo - Tri Suci Katili; Harun Blongkod; Lukman Pakaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the effect of implementing the Regional Government Information System (SIPD) on the quality of financial reports in the Regional Apparatus Organizations (OPD) of Gorontalo Province. SIPD is implemented as an effort to increase transparency, accountability and efficiency in regional financial management. This research uses a quantitative approach with statistical analysis methods to examine the relationship between SIPD implementation and the quality of financial reports. The research results show that the implementation of SIPD has a positive and significant effect on the quality of financial reports in the Gorontalo Province OPD. Factors such as human resource skills, technological infrastructure, and regulatory effectiveness also contribute to the success of SIPD implementation. These findings emphasize the importance of optimizing information systems in supporting more transparent and accountable financial governance in regional government environments.